Track & field coaching essentials. USA Track & field level 1 coach education manual (Human Kinetics, 2015)
Coaching track and field is a unique challenge. The number of events, the specific technical skills to teach in each one, the event- and athlete-tailored training programs required for performing at a high level, and the planning and organization needed for practicing and competing effectively as a team can be difficult for even the most educated and experienced coaches.